2015
DOI: 10.1186/s12876-015-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased PCSK9 expression in human hepatocellular carcinoma

Abstract: BackgroundThe management of hepatocellular carcinoma (HCC) is limited by the lack of adequate screening biomarkers and chemotherapy. In response, there has been much interest in tumor metabolism as a therapeutic target. PCSK9 stimulates internalization of the LDL-receptor, decreases cholesterol uptake into hepatocytes and affects liver regeneration. Thus, we investigated whether PCSK9 expression is altered in HCC, influencing its ability to harness cholesterol metabolism.MethodsThirty-nine patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 35 publications
4
59
1
Order By: Relevance
“…Decreased PCSK9 and increased LDLR expression have been demonstrated in HCC tissues, supporting a constant cholesterol supply in the HCC microenvironment [33]. HMGCR is the rate-limiting enzyme in de novo synthesis of cholesterol in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased PCSK9 and increased LDLR expression have been demonstrated in HCC tissues, supporting a constant cholesterol supply in the HCC microenvironment [33]. HMGCR is the rate-limiting enzyme in de novo synthesis of cholesterol in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…225 Increased expression of LDL-R was found in HCC compared with adjacent liver tissue. 226 N-succinyl chitosan NPs were coupled with LDL for target co-delivery of cholesterol-conjugated siRNA and DOX by Zhu et al 227 The LDL-decorated delivery system exhibited superior cytotoxicity against HepG2 cells over non-targeted system and also manifested enhanced liver tumor-targeting effects and relatively lower systemic toxicity in mice bearing hepatoma cell tumor, suggesting their potential for HCC therapy. LDL was also utilized to modify osthole-loading N-succinyl chitosan NPs, attaining high targeting efficacy indicated by investigations in vitro and in vivo.…”
mentioning
confidence: 99%
“…However, only a few studies have reported the relationship between PCSK9 and cancer [6,8]. One study on HCC reported a decrease in PCSK9 expression in human HCC tissues but did not clarify the speci c signi cance of low PCSK9 expression levels in the carcinogenesis and development of HCC [4]. Our study has demonstrated, for the rst time, that PCSK9 can interact with GSTP1, affect JNK phosphorylation levels, and inhibit HCC proliferation, which is of great signi cance for further understanding the function of the PCSK9 protein and suggests that PCSK9 may serve as a therapeutic target for patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCSK9 has been reported to play an important role in a variety of biological processes, including the in ammatory response, immune response, metabolism, cell cycle, and apoptosis [1][2][3]. A previous study reported that PCSK9 expression in HCC tissues is lower than that in paracancerous tissues [4], and our previous study found that Chinese kiwifruit root extract had the effect of inhibiting the development of hepatocarcinoma cells, and PCSK9 is the key molecule of the Chinese herbal extract to inhibit the proliferation of liver cancer cells [5]. In addition, PCSK9 has been found to be closely related to the occurrence and development of a variety of tumors, including melanoma, prostate cancer, and lung cancer.…”
Section: Introductionmentioning
confidence: 99%